Green Politics and Climate Change: Analysis of Political Party Strategies on Environmental Issues - Ananta, Yorasakhi; Fitri, Salsabila Dwi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
This article analyzes the strategies of political parties in Indonesia in responding to climate change issues through a green politics approach. The research was conducted using a qualitative method based on literature studies and document analysis of manifestos, campaign programs, and party statements ahead of the 2024 General Election. The results show that although environmental issues have begun to be included in the political agenda, their implementation tends to be symbolic and inconsistent. Factors such as the influence of economic elites, weak public pressure, and minimal ecological literacy also hamper the implementation of progressive policies. To strengthen green politics, internal party reform and active community participation are needed in monitoring and promoting the environmental agenda in a sustainable manner.